Spelling Errors of Omani EFL Students - Sheikha A. Al-Bereiki; Abdo M. Al-Mekhlafi (Sultan Qaboos University, 2015)
The purpose of this study was to explore the types of spelling errors students of grade ten make and to find out whether there were any significant differences between males and fe- males with respect to the types of spelling errors made. The sample of the study included 90 grade ten students from four different schools in North Batinah. The researchers manipulated the use of a test that consisted of two questions: an oral dictation test of 70 words with a contex- tualizing sentence and a free writing task. The misspellings were classified into nine different types. The findings revealed that the most common spelling errors among Omani grade ten stu- dents were vowel substitution, then came vowel omission in the second place and consonant substitution in the third place. Male students omitted more vowels than female students while females made more true word errors than their male counterparts. In light of the findings, the study presents some recommendations and suggestions for further studies.